Change Management for Semantic Web Services - Liu, Xumin; Akram, Salman; Bouguettaya, Athman (Springer eBooks., 2011)
Change Management for Semantic Web Services provides a thorough analysis of change management in the lifecycle of services for databases and workflows, including changes that occur at the individual service level or at the aggregate composed service level. This book describes taxonomy of changes that are expected in semantic service oriented environments. The process of change management consists of detecting, propagating, and reacting to changes. Change Management for Semantic Web Services is one of the first books that discuss the development of a theoretical foundation for managing changes in atomic and long-term composed services. This book also proposes a formal model and a change language to provide sufficient semantics for change management; it devises an automatic process to react to, verify, and optimize changes. Case studies and examples are presented in the last section of this book.